A flexible and compact tri‐band antenna for vehicular wireless video transmission systems. Issue 9 (7th May 2021) - Xu, Hao; Chen, Zhijiao; Zhao, Zhenyu; Liu, Haiwen; Zhu, Shuangshuang
Abstract: In this article, a flexible and compact tri‐band microstrip antenna is proposed for vehicular wireless applications. Triangular embedded radiators are employed to provide design freedom and minimize antenna size. Aiming at the bending demand and conformal modules, flexible polyimide‐based substrate is used for antenna fabrication. The measured results show that the proposed antenna operates at 1, 2.4, and 3.5 GHz, covering wireless local area network (WLAN) HaLow, WLAN, and world interoperability for microwave access bands. Benefited from its tri‐band operation, compact structure and flexible design, the proposed antenna is suitable to be integrated to wireless systems. The antenna occupies a compact size of 68 mm × 71 mm × 0.11 mm. For verification, the proposed antenna is integrated to a wireless high‐definition video transmission system. The system is composed of a 5‐megapixel camera, a video processor, a wireless network card, the tri‐band flexible antenna, and wireless terminals like smart phones. The measured results confirm high efficiency, mobility, and stability of the wireless video transmission system with the proposed antenna.